Gambaran Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa dan CAPD di RSUP Prof. Dr. R. D Kandou - Tanos, George Alex; Masi, Gresty; Fitriani (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background. The prevalence of CKD is increasing in Indonesia. Kidney replacement therapies such as HD and CAPD are essential for CKD patients. However, these therapies can affect patients' quality of life and result in significant lifestyle changes and side effects. Objective. This study aims to describe the quality of life of CKD patients undergoing HD and CAPD at Prof. Dr. R. D. Kandou Teaching Hospital. Methods. A descriptive analytical cross-sectional study was conducted using non-probability accidental sampling. The sample consisted of 72 respondents (60 HD patients and 12 CAPD patients). Data was collected through demographic questionnaires and the WHOQOL-Bref questionnaire. Results. In the physical health dimension, the majority of HD patients (76.7%) and all CAPD patients (100%) had good quality of life. Similar trends were observed in the psychological health dimension, with most HD patients (91.7%) and all CAPD patients (100%) reporting good quality of life. The majority of HD patients (91.7%) and CAPD patients (91.7%) also had good quality of life in the social relationship dimension. In the environmental dimension, the majority of HD patients (98.3%) and CAPD patients (83.3%) had good quality of life. Discussion. Both HD and CAPD patients generally have good quality of life. However, some patients still experience lower quality of life due to the impact of their illness on their physical, psychological, social, and environmental well-being. Conclusion. The majority of CKD patients undergoing HD and CAPD have good quality of life. Nevertheless, special attention is required for patients with a lower quality of life. Keywords: CAPD; Chronic Kidney Disease; Hemodialysis; Quality of Life